The research landscape of ferroptosis in the brain: A bibliometric analysis - Miao, Mengrong; Han, Yaqian; Wang, Yangyang; Yang, Yitian; Zhu, Ruilou; Sun, Mingyang; Zhang, Jiaqiang (Frontiers in Pharmacology, 2022)
Background: Ferroptosis is a newly proposed concept of programmed cell death and has been widely studied in many diseases during the past decade. However, a bibliometric study that concentrates on publication outputs and research trends of ferroptosis related to the brain is lacking. Methods: We retrieved publication data in the field of ferroptosis in the brain from the Web of Science Core Collection on 31 December 2021. A bibliometric analysis was performed using VOSviewer and CiteSpace software. Results: Six hundred fifty-six documents focusing on ferroptosis in the brain were published from 2012 to 2021. The number of publications in this field has shown a steady increase in recent years. Most publications were from China (338) and the United States (166), while the most productive organizations were at the University of Melbourne (34) and University of Pittsburgh (23). Ashley I. Bush was the most productive author, while Scott J Dixon was the most co-cited author. The journal Free Radical Biology and Medicine published the most articles in this field, while Cell was the most cited journal. Among 656 publications, top 10 cited documents were cited at least 300 times. Among the top 20 references with the strongest citation bursts, half of the papers had a burst until 2021. The keywords analysis suggests that the top 20 keywords appeared at least 40 times. Additionally, “amyloid precursor protein” was the keyword with strongest bursts. Conclusion: Research on ferroptosis in the brain will continue to be highly regarded. This study analyzed the research landscape of ferroptosis in the brain and offers a new reference for researchers in this field.